2015
DOI: 10.1080/15205436.2015.1051234
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Decade Retrospective on the Hostile Media Effect

Abstract: Some 30 years ago, Vallone, Ross, and Lepper (1985) conducted a pioneering study of the hostile media effect in which they demonstrated that partisans perceive media coverage as unfairly biased against their side. Over the ensuing decades, scores of experiments and surveys have extended their findings, demonstrating hostile media effects in a variety of domains. Taking the measure of the research more than 30 years later by systematically reviewing the many studies conducted in different locales, this article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
137
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 141 publications
(152 citation statements)
references
References 75 publications
(142 reference statements)
6
137
0
9
Order By: Relevance
“…Specifically, individuals who held negative beliefs and attitudes to a specific news report were found to be more likely to develop hostile media bias (Giner‐Sorolla & Chaiken, ). Perloff () also strengthened the claim that prior attitude, or a previously held belief about a topic, remains an important factor in how individuals perceive bias. Further, it has been pointed out that individuals viewed information in the news report based on different standards and they thought that self‐aligning (i.e., congruent) opinions were more correct than those that differed from their own (i.e., incongruent) opinions (Gunther & Schmitt, ).…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations
“…Specifically, individuals who held negative beliefs and attitudes to a specific news report were found to be more likely to develop hostile media bias (Giner‐Sorolla & Chaiken, ). Perloff () also strengthened the claim that prior attitude, or a previously held belief about a topic, remains an important factor in how individuals perceive bias. Further, it has been pointed out that individuals viewed information in the news report based on different standards and they thought that self‐aligning (i.e., congruent) opinions were more correct than those that differed from their own (i.e., incongruent) opinions (Gunther & Schmitt, ).…”
Section: Literature Reviewmentioning
confidence: 90%
“…The hostile media phenomenon contends that individuals, especially strong partisans and individuals who are highly involved with an issue, are likely to perceive neutral media coverage as demonstrably biased against their point of view (Vallone, Ross, & Lepper, ), which in turn, lower trust in media and strengthen political polarization. This perceptual bias explains the relationships between attitudes, public opinion, and perceptions of media effects (Perloff, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, researchers found that people spend more efforts on scrutinizing attitude-incongruent versus attitude-congruent information to defend existing beliefs (Edwards & Smith, 1996). Moreover, research on "hostile media effects" suggests that people may perceive attitude-challenging media as unfairly biased against their own viewpoints (Perloff, 2015). In two studies, negative perceptions of refugees predicted biased media perceptions, suggesting that need deprivation may indeed be involved in such effects (Arlt, Dalmus, & Metag, 2018;Arlt & Wolling, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The measure of media congruency (evaluation of news media reporting) is viewed as an alternative way to measure the subjective perception of the opinion climate. Even if this is not a straightforward question of how a respondent's own opinion is related to the general opinion, we know from previous research that people tend to generalize media content to the general view of societal problems and their effect on public opinion (Gunther & Storey, 2003;Perloff, 2015;Schulz & Roessler, 2012). Evaluation of news media reporting can therefore be seen as a proxy for the respondents' views on the opinion climate in society.…”
Section: Data Collectionmentioning
confidence: 99%